Chemical composition and antioxidant activity of acetone extract from Chlorophytum laxum - Nguyen, Hanh Thi Dieu; Nguyen, Duc Hoa; Ngo, Thanh Dat; Nguyen, Ngoc An; Nguyen, Ngoc Thuan; Nguyen, Quoc Hung; Pham, Tan Viet (Journal of Phytology, 2025)
The genus Chlorophytum is renowned for its ornamental value and applications in traditional medicine, especially in tropical regions. This study presents the first report on the phytochemical screening, volatile compound profiling, and antioxidant activity of acetone extracts from the leaves and roots of Chlorophytum laxum. Gas chromatography-mass spectrometry (GC-MS) analysis revealed 34 and 22 volatile compounds in the leaf and root extracts, respectively. In the leaf extract, the major components identified were 2-pentanone, 4-methoxy-4-methyl-; 1,2,4-butanetriol; 9,12,15-octadecatrienoic acid, (Z,Z,Z)-; n-hexadecanoic acid; neophytadiene; and 5-hydroxymethylfurfural. Conversely, the root extract predominantly contained 2-pentanone, 4-hydroxy-4-methyl-, and 5-hydroxymethylfurfural. Furthermore, the antioxidant capacity was evaluated using the ABTS radical scavenging assay. The leaf and root acetone extracts exhibited IC50 values of 29.82±1.08 μg/mL and 52.46±2.51 μg/mL, respectively. These findings suggest potential applications for C. laxum in pharmaceutical and food industries and warrant further investigation into its bioactive properties and potential utilization.